Strategi Komunikasi Imigrasi dalam Membangun Persepsi Publik terhadap Layanan Paspor di Era Digital - Ghanim, Muhammad Hafiz; Mastur, Anida Sri Rahayu; Priyatno, Mas Budi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
In the realm of public services, passport issuance has become increasingly dependent on effective communication strategies to foster positive public perception, particularly in the digital era. Misinformation, unclear service procedures, and the rise of fraudulent online accounts have underscored the need for transparent, timely, and interactive communication. This study aims to examine how immigration authorities can integrate digital platforms and two-way communication to build public trust and institutional credibility. Employing a qualitative literature review, relevant scholarly articles, books, official documents, and credible online sources were analyzed based on inclusion criteria focusing on communication strategies, public service quality, and digital engagement practices. The findings reveal that effective public communication in passport services requires: the selection of appropriate and culturally inclusive media channels, proactive and consistent information delivery, the use of interactive features such as chatbots, online complaint systems, and social media engagement, and empathetic, responsive service delivery. The integration of digital tools with symmetrical two-way communication, supported by the SERVQUAL dimensions of tangibles, reliability, responsiveness, assurance, and empathy, significantly enhances public trust and strengthens the institution’s image as transparent, professional, and citizen-oriented. This study highlights the strategic value of aligning technological innovation with human-centered communication practices to meet evolving public expectations in immigration services.